OC-015 Nicorandil Does not Worsen Non-Variceal Upper Gastrointestinal Bleeding (NVUGIB) in Patients Taking Aspirin or Antithrombotic Drugs (ATDs). (17th August 2016) - Taha, AS; McCloskey, C; Craigen, T; Simpson, A; Angerson, WJ
Abstract : Introduction: Nicorandil is a vasodilatory drug that has the dual properties of a nitrate and K+ATP channel agonist. It is often added to ATDs in the management of angina. In light of some case reports, its manufacturer and the medicines regulatory agencies have issued cautions that it can cause mucosal ulcers, perforation and bleeding, and that these might be worse in users of aspirin. We therefore aimed to investigate the possibility that NVUGIB is more severe in patients using ATDs plus Nicorandil than ATDs alone. Methods: Patients presenting with NVUGIB and using ATDs plus Nicorandil (n = 59) were compared to those using ATDs alone (Controls; n = 1056) with respect to haemoglobin level, Blatchford UGIB risk score, composite endoscopy score (covering lesions in the oesophagus, stomach and duodenum), need for blood transfusion, length of hospital admission, and 30 day mortality. ATDs included low dose aspirin, clopidogrel, dipyridamole, warfarin and heparin. Results: Table 1, below, summarises the outcomes of NVUGIB and the characteristics of patients using ATDs alone vs. those using ATDs plus Nicorandil. Age and haemoglobin are shown as mean (SD), the other interval variables as median (interquartile range) and binary variables as percentage (number). The final column shows differences between groups (Nicorandil minus control) with 95% confidence intervals. All differences were statistically insignificant (P > 0.05, Student's t, Mann-Whitney and Fisher's exact tests as appropriate). Conclusion: Patients taking ATDs plus Nicorandil were well matched demographically with controls taking ATDs alone. The confidence intervals place a modest upper limit on any exacerbation of NVUGIB by Nicorandil as manifested by reduced haemoglobin and increased need for transfusion. The intake of Nicorandil does not seem to worsen the severity or the outcomes of NVUGIB. These findings, therefore, do not justify discontinuing Nicorandil in patients with angina and presenting with NVUGIB while taking ATDs. Disclosure of Interest: None Declared